2013
DOI: 10.3389/fnhum.2013.00777
|View full text |Cite
|
Sign up to set email alerts
|

Neural entrainment to rhythmic speech in children with developmental dyslexia

Abstract: A rhythmic paradigm based on repetition of the syllable “ba” was used to study auditory, visual, and audio-visual oscillatory entrainment to speech in children with and without dyslexia using EEG. Children pressed a button whenever they identified a delay in the isochronous stimulus delivery (500 ms; 2 Hz delta band rate). Response power, strength of entrainment and preferred phase of entrainment in the delta and theta frequency bands were compared between groups. The quality of stimulus representation was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
180
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 124 publications
(202 citation statements)
references
References 48 publications
15
180
5
2
Order By: Relevance
“…Therefore, the consistent timing difference could have cascading consequences for the optimal encoding of phonetic information by these children. Individual differences in preferred phase were indeed related to performance in a phoneme deletion task 100 . Importantly, different phase alignment between groups was not found in a visual speech control condition 100 .…”
Section: Amplitude Modulation (Rise-time) Deficitmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, the consistent timing difference could have cascading consequences for the optimal encoding of phonetic information by these children. Individual differences in preferred phase were indeed related to performance in a phoneme deletion task 100 . Importantly, different phase alignment between groups was not found in a visual speech control condition 100 .…”
Section: Amplitude Modulation (Rise-time) Deficitmentioning
confidence: 98%
“…Individual differences in preferred phase were indeed related to performance in a phoneme deletion task 100 . Importantly, different phase alignment between groups was not found in a visual speech control condition 100 . Nevertheless, RL-matched EEG studies are currently missing.…”
Section: Amplitude Modulation (Rise-time) Deficitmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies with adults and children with developmental dyslexia have consistently reported atypical neural activity related to auditory processing (Abrams et al, 2009, Lehongre et al, 2011, Poelmans et al, 2012, Hornickel and Kraus, 2013, Power et al, 2013, Lizarazu et al, 2015). However, none of these recent auditory studies has used a reading level (RL) match control group, an important research design for helping to distinguish cause from effect in studies of developmental disorders (Goswami, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Power et al (2013) administered the AV rhythmic speech paradigm developed by Power et al (2012) to English-speaking children with dyslexia. They reported that, compared to age-matched control children, the children with dyslexia showed a different preferred phase of entrainment in the delta band, in response to both the auditory and the auditory-visual stimulus streams.…”
Section: Introductionmentioning
confidence: 99%